PENGARUH KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN MULTIFUEL BOILER PADA PT. LONTAR PAPYRUS PULP AND PAPER INDUSTRY - Sakinah AS; Anang Suprianto (Universitas Batanghari, 2017)
The average increase in the number of employees Part Multifuel Boiler PT. Lontar Papyrus Pulp & Paper Industry as much as 0.56%. The average percentage of the absence of leadership in a meeting held in the last five years as much as 14.27%. The average employee productivity developments Part Multifuel Boiler at PT. Lontar Papyrus Pulp & Paper Industry at 31.333. Indicators for assessing leadership include: have a fairly high intelligence, stable emotions, face human intelligence, organizing skills and management skills. Indicators assessing productivity include: the ability, improve the results achieved, morale, self-development, quality and efficiency. PT. Lontar Papyrus Pulp & Paper Industry which is a company engaged in Pulp & Paper thats end product of PT. Lontar Papyrus Pulp & Paper Industry, which in the final product the company is supported by Section Multifuel Boiler manage Steam Power ( Power Plant) to supply its electricity needs. Results SPSS 23 get the regression equation Y = 0.473 + 0.892 X. domination leadership on improving employee productivity Section Multifuel Boiler at PT. Lontar Papyrus Pulp & Paper Industry as much as 76.9% while the remaining 23.1% is caused by other factors. There is a significant relationship between the leadership on employee productivity Section Multifuel Boiler at PT. Lontar Papyrus Pulp & Paper Industry. This statement proved of t count 18.341> t table value 1.9840, with a significant 0.00 <0.05. Leadership and employee productivity Section Multifuel Boiler at PT. Lontar Papyrus Pulp & Paper Industry high . According to test the hypothesis test is known that there is significant influence among the leadership on employee productivity Section Multifuel Boiler at PT. Lontar Papyrus Pulp and Paper IndustryKeyword : multifuel boiler, productivity